Developing a novel TaqMan qPCR assay for optimizing Salmonella Pullorum detection in chickens - Hao Wang; Xiamei Kang; Longhai Yu; Haijian Wang; Anja Müller; Corinna Kehrenberg; Yan Li; Min Yue (Veterinary Quarterly)
Salmonella Pullorum, the causative agent of pullorum disease, posing a significant threat to the global production of poultry meat and eggs. However, existing detection methods have substantial limitations in efficiency and accuracy. Herein, we developed a genomic deletion-targeted TaqMan qPCR assay for identification of Salmonella Pullorum, enabling precise differentiation from other Salmonella serovars. The assay’s detection limit was 5 copies/μL of plasmid and 4 CFU/μL of bacterial DNA. Furthermore, we collected 676 chicken samples from an established infection model to compare the performance of the TaqMan qPCR assay with traditional bacterial culturing and antibody-based detection approaches. With superior sensitivity and specificity, the newly developed method detected over 80% of positive chickens, significantly outperforming the two conventional methods. Moreover, we proposed a combined framework that incorporates the advantages of TaqMan qPCR assay and antibody detection method, further enhancing the detection rate of positives to 92%. Additionally, to address the frequent aerosol contamination of amplification products in laboratory settings, we devised an easy-to-deploy anti-contamination system based on T7 exonuclease. Overall, the T7 exonuclease-assisted TaqMan qPCR assay will not only upgrade the current detection for pullorum disease, but also exemplify the feasibility of targeting specific genomic deletions for pathogen detection.